Effect of diet on carnitine and lipid metabolism with particular reference to Kwashiorkor - Da Cruz, Isabel Maria Rosa (My University, 1991)
Carnit ine plays a role in the transport of act iva ted long chain fatty acyl groups from the site of activation to the site of beta-oxidation in the mitochondria. Endogenous synthesis of ca.rnitine from the amino acids methionine and lyslne~ takes place mainly in the liver. Fl.'om i:here free and acyl caen.itine are re 1eased into the blood and transported to other tissues. A few studies have indicated that poor nutrit.ional status may Idad to carnitin€ defic'lency. There is a high prevalence of Itwashiorkol; p a. prot ein-enel~gy de f Ie 1an t state p among's t the 1::1a1ck popul at ion in Southern A:h~ica , but at present littie is known concerning carnitine and i is poasible effects on lipid met abo I I sm, Furthermore ther\';! have been relatively few studies concerning the effects of different diets on serum e arn i t Lne and lipid. So fa.r no reports have been pub l I shed concerning the e fisc t,a 0.£ l\&,li, ze meal as a a t apI e di is t , Thi s is 'highly relevarAt in the South African context. The aims of the present study WEll'e to oompare serum carnitine, protein and lipids in blaclt and white Sou.th African adu l ts, to evah.ls1:e tbe effect of a high maI Z~ diet (10W-Pl~otein) on. heal thy adu] t IS and to mves t ignte these parametet's in chi Idren wi th Itws.shiorltol' as compa.!' ed wi th normal chi Idl'en as well as to assess the re.sponse to treatment in the :aut!"i tionally depl~ived group. tn the p'reserl't study no ma]or c'u. fferences wel;e observed '!:nlltvJ'een the diffel~·ent adult population groups; va l ue s for "ormal children wer8 In general within similar lahlss. A change to a IDw~pratein diet in healthy whi t e adu l t s produced signi. ficant di ffer811ces in carn. I t t ne and the proteins and lipiiis measured. The values "btained for the lrwashiorlwl' chi Ldren showed aigniticaA~t Changes as compared with no rma l eht t dr en, En par t f cut s« cam it Ine and total phospholipid eonc~ nt'J.'fations wel'l;; sig'oi Hcsnt 11 reduced and the percentag~ of doc(llsatetra~noic acid (22:4) was increased. The results obtained sugg~~t that there may be impaired o2idatioil of lipids' in ktt'H1Shiol'KOr and the deficiency of carnt ti ne may provide an exp Lanat ion for the aceumuIat f cn of fats in the livers of Itwashiorltol' patients. The de or e a se in total phospholipid concentration with a lt erat Lons in the lecithin fatty acid distribution in the ~hildren suggest that there may be changes ih membrane fluidity and fleXibility.